Investigation of human anthrax outbreak in Koraput district of Odisha, India - Debaprasad Parai; Matrujyoti Pattnaik; Hari Ram Choudhary; Arun Kumar Padhi; Swati Pattnaik; Sunita Jena; Subrat Kumar Sahoo; Usha Kiran Rout; Ankita Padhi; Niranjana Sahoo; Sangram Biswal; Soumesh Kumar Padhi; et al. (Travel Medicine and Infectious Disease, 2023)
Background: Anthrax is a zoonotic infection resulting from the bacteria Bacillus anthracis. Humans contract cutaneous anthrax by coming into contact, and gastrointestinal (GI) anthrax by consumption of infected animals or animal products. An outbreak investigation was conducted to confirm the occurrence of the anthrax outbreak, comprehend its extent, understand the epidemiological characteristics, identify the outbreak's cause, and propose control measures. Methods: A descriptive epidemiology was carried out for this outbreak investigation. We defined a suspected human cutaneous anthrax case as appearance of skin lesions and symptoms (itching/redness/swelling) and a suspected case of GI anthrax as appearance of diarrhoea/abdominal pain/vomiting in a resident of Koraput district after being associated with slaughtering and/or consumption of carcass during 5th April to 15th May 2023. The etiological hypothesis was formulated using descriptive epidemiological methods. Laboratory confirmation was performed by real-time polymerase chain reaction (RT-PCR). Statistical analyses were conducted using SPSS 25. Results: A total of 47 clinically suspected anthrax cases were identified during the outbreak in five villages of Koraput district in Odisha. The epidemic curve indicated multiple point-source exposures starting from 13th April 2023. About 10 cases were identified by RT-PCR testing as confirmed cases of anthrax. No death was recorded in this outbreak investigation. Conclusions: Based on a thorough examination of epidemiological survey results and laboratory findings, we conclude that the outbreak was of human cutaneous and GI anthrax. Exposures from handling dead animals were associated with cutaneous anthrax, whereas eating uncooked meat of dead sheep was associated with gastrointestinal anthrax.